2020
DOI: 10.1139/cjfas-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Otolith microchemistry and acoustic telemetry reveal anadromy in non-native rainbow trout (Oncorhynchus mykiss) in Prince Edward Island, Canada

Abstract: This study examined the migratory patterns of introduced rainbow trout (Oncorhynchus mykiss) in three rivers in Prince Edward Island, Canada, using acoustic telemetry and otolith microchemistry. Only 6% of acoustically tagged fish in three river systems left coastal embayments. A cohort of rainbow trout in all three rivers entered saline waters. Habitat use differed among migrants in the three rivers, as Montague River fish occupied estuary habitat (mean 20.79 PSU) more often than West River and Dunk River fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
(114 reference statements)
1
10
0
Order By: Relevance
“…We consider these results preliminary given the small number of putative migrants detected. Nevertheless, this outcome is consistent with some tagging studies of introduced Rainbow Trout in eastern Canada, which have shown limited movement into salt water and a slow rate of invasion to adjacent coastal watersheds (Roloson et al 2018, 2020). From a conservation perspective, evidence that coastal migration is possible for southwestern Alaska Rainbow Trout warrants further study because it reflects a life history polymorphism that increases opportunities for foraging, overwintering, and connectivity, thus improving population resilience (Kendall et al 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We consider these results preliminary given the small number of putative migrants detected. Nevertheless, this outcome is consistent with some tagging studies of introduced Rainbow Trout in eastern Canada, which have shown limited movement into salt water and a slow rate of invasion to adjacent coastal watersheds (Roloson et al 2018, 2020). From a conservation perspective, evidence that coastal migration is possible for southwestern Alaska Rainbow Trout warrants further study because it reflects a life history polymorphism that increases opportunities for foraging, overwintering, and connectivity, thus improving population resilience (Kendall et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Variation also exists within these two general strategies (Quinn and Myers 2004). For example, anadromous individuals typically spend one or more years in the open ocean, but in some populations the marine migration may only last a few months in coastal marine or estuarine habitat (e.g., Pavlov et al 2008; Peterson et al 2017; Roloson et al 2020). Freshwater resident individuals can exhibit lacustrine, fluvial, and adfluvial life histories demonstrating seasonal migrations for foraging and reproduction (e.g., Meka et al 2003).…”
Section: Figurementioning
confidence: 99%
“…Specifically, most American studies were located either in the Laurentian Great Lakes or Mississippi River watersheds. Given studied localities, most of the published applications of otolith chemistry in invasion management were conducted in freshwater, with only a handful of studies conducted in estuarine habitats (Thibault et al 2010;Honda et al 2012;Araya et al 2014;Roloson et al 2020). Applications of otolith chemistry to invasive fishes in marine systems were not encountered in the literature search, which is not the case in the broader applications of otolith chemistry, where estuarine and marine habitats are estimated to represent 56.4% of published management-oriented applications of otolith chemistry (Carlson et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessment of the natal origin was used to (in decreasing order) determine the number and identity of potential natal sources (Love et al 2019;Whitledge et al 2019), to identify reproduction hotspots (Macdonald et al 2010;Wolff et al 2012;Crook et al 2013) or to identify the most likely source populations of illegal stocking (Wolff et al 2012;Bourret and Clancy 2018;Love et al 2019). Otolith chemistry has been used to assess migration behaviour of invasive fishes (21,4%, n = 6), mainly to determine the frequency of movement between habitats-such as between main channel and wetlands- (Araya et al 2014;Rude et al 2017), the invader population expansion strategy (Limburg and Siegel 2006;Thibault et al 2010) or the seasonal or lifetime migratory behaviour of an invasive fish (Roloson et al 2020;Morissette et al 1 3…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ability to establish populations in high salinity environments could potentially increase the overall population size, connectivity and ultimately, the negative impacts of this species on estuarine organisms. Other non-native freshwater species such as pike Esox lucius and rainbow trout Oncorhynchus mykiss use brackish waters for reproduction and foraging, as migration corridors to new habitats or to avoid stressful abiotic conditions [13,14]. The ability of blue catfish to establish populations in high salinity habitats is a concern among resource managers.…”
Section: Introductionmentioning
confidence: 99%